Prabowo's Victory: How Influencers Shaped the 2024 Election - Nugraha, Surya; Ridwan, Muhammad Handzalah; Mardana, Fahriza; Lisnarini, Narah (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
This research investigates the role of influencers in political communication, particularly in the success of Prabowo-Gibran during the 2024 Presidential Election. The study addresses the increasing impact of social media personalities on political campaigns. Through qualitative analysis, it explores the strategies influencers use to influence public opinion and rally support for political figures. The results show that influencers serve as intermediaries, bridging the gap between the government and the public while also promoting greater public accountability. Additionally, their ability to engage audiences through relatable and emotionally charged content plays a significant role in shaping public views of candidates. This research underscores the evolving relationship between digital platforms and political processes, highlighting the importance of balancing popularity with expertise in governance. Contribution: The study also reveals the importance of relatable, emotionally charged content in shaping public perceptions of political candidates, underscoring the increasing significance of digital platforms in political processes and the need to balance popularity with expertise in governance.